Effects of Antioxidant and Dietary Fiber Content of Fresh and Oven-Dried Red Pitaya Fruit (Hylocereus Polyrhizus.) on Hypercholesterolemic and Insulinresistant Rats - Omidizadeh, Alireza (2009)
This study was designed to investigate the effect of antioxidant content and soluble dietary fiber of red pitaya fruit (Hylocereus polyrhizus) on hypercholesterolemic and insulin resistant rats. In the laboratory, red pitaya fruit (Hylocereus polyrhizus) was subjected to five different thermal processes: oven drying at 95°C for 30min, oven drying at 95°C for 60min, oven drying at 105°C for 60min, drum drying, and spray drying. Total phenolic contents, radical scavenging activity, antioxidant activity and dietary fiber contents of the fresh and processed red pitaya were subsequently determined. The results of the study revealed that the length of the temperature time was more damaging to total phenolic contents, radical scavenging, and antioxidant activity of this fruit compared to high heating temperatures. The effect of long time (30- 60 minutes) oven heating temperatures (95-105°C) on antioxidant parameters of red pitaya were highly significant compared to fresh one (p < 0.05). Among all of the heating temperatures, drum drying was the best method for preservation of total phenolic contents, radical scavenging and antioxidant activity with 7%, 8%, and 13% reduction, respectively; and 95°C for 30 minutes oven drying was the best process for dietary fiber parameters with 8%, 0%, and 2% decreases in soluble, insoluble, and total dietary fibers, respectively. From the laboratory studies, two thermal processed pitaya with distinct proportions of phenolic contents, radical scavenging activity, and soluble dietary fibers were determined. The first thermal processed pitaya was the heated one at 95°C for 30 minutes and contained low phenolic contents and radical scavenging activity with almost intact soluble dietary fiber. The second one was heated pitaya at 105°C for 60 minutes with low in all of the studied biologically active components. These two thermal processed pitayas along with fresh pitaya were tested, as supplements, on high cholesterol (hypercholesterolemic) and high fructose-fed (insulin resistant) rats during 6 weeks treatment in the curative studies. The results showed that fresh red pitaya decreased total cholesterol, LDL-Cholesterol, glucose level, and also increased the serum total antioxidant power in hypercholesterolemic rats, significantly (p < 0.05). Moreover, the atherosclerotic changes induced by cholesterol supplement in rats were reversed by fresh pitaya. The hypocholesterolemic and anti-atherogenic effects of both oven-heated pitaya at 95°C for 30 min, and oven-heated pitaya at 105°C for 60 min contained low phenolic contents and radical scavenging activity were not significant. Fresh red pitaya could significantly reduce insulin level, insulin/glucose ratio, triglyceride, total cholesterol, and glucose level (p < 0.05) in insulin resistant rats. Besides, it improved glucose intolerance and increased the serum total antioxidant capacity, significantly (p < 0.05). The intima-media thickness of the abdominal aorta was significantly lower in fresh pitaya-fed rats than the positive control (p < 0.05), and there were no noticeable changes in their endothelial layer. The anti-atherogenic and anti-dyslipidemic effects of heated pitaya 95°C for 30 min contained low content of phenolic contents and radical scavenging activity was not significant, but it decreased insulin level, insulin/glucose ratio, glucose level and glucose intolerance, significantly (p < 0.05). The heated pitaya 105°C for 60 min contained low content of phenolic contents, radical scavenging activity, and soluble dietary fiber had no effective role in improving the insulin resistance, dyslipidemia and atherogenesis. The data clearly showed that fresh red pitaya (that its antioxidants and dietary fibers remained intact) was capable of attenuating the hypercholesterolemia, insulin resistance and atherosclerotic changes induced by cholesterol and fructose supplement in rats. The hypocholesterolemic and anti-atherogenic effects of heated pitaya 95°C for 30 min contained low content of phenolic contents and radical scavenging activity, but almost intact soluble dietary fiber were not significant, but it improved insulin resistance (hyperinsulinemia). The heated pitaya 105°C for 60 min contained low content of phenolic contents, radical scavenging activity, and soluble dietary fiber had no effective role in improving the hypercholesterolemia, insulin resistance and atherogenesis. To conclude, antioxidant content of red pitaya fruit is very important for ameliorating dyslipidemia in hypercholesterolemic and insulin resistant rats; and red pitaya without enough antioxidant and soluble dietary fiber content is not able to play an effective role in the management of hypercholesterolemia and insulin resistance. These results will be useful for nutritionists and food scientists to use this tropical fruit as a nutritious product in the food industry to safeguard health and manage the hypercholesterolemia, insulin resistance and metabolic syndrome.